Independence of women through sewing skills - Sibarani, Magdalena; Dewi , Elita (Talenta Publisher, 2019)
Facing an era of increasingly fierce competition, a person is required to have a high entrepreneurial spirit so that he can run a business that he lives well. Thus we must be able to see market opportunities and desires in terms of needs and selling points that we will offer to consumers.Â Entrepreneurs in sewing services are still promising. Even though now there are a lot of apparel production, stitching services are still needed by consumers. Because there are some risks in purchasing apparel that are usually accepted by buyers. Not all clothes fit to be worn by consumers. Especially for people who have different body postures from the standards of people in general, such as too small or too fat. Besides that, there are certain clothes models and materials that are more comfortable when used from ordinary stitches, rather than in the form of apparel manufactured by the factory. For example, traditional clothing, brocade fabrics, suits, kebaya, woven fabrics and others. In connection with this, it is felt necessary to provide training to improve the skills of clothing tailors to be able to produce clothes that are in accordance with market desires efficiently and effectively. Besides improving skills in spraying and embroidering in order to have the ability to compete in terms of quality, models, variations in motifs and the color combination of clothing produced, so as to create and have a lot of marketing networks. The need for training that enables tailor clothing to calculate total sales revenue and total costs so that they are able to know how much profit is obtained per piece of clothing.Â It is hoped that after the mentoring, the partners will be more knowledgeable, able to apply this knowledge in their daily work and transmit this knowledge to other dressmakers. Thus, all dressmakers will develop more, become more economically independent, increase in income, tailor clothes become more productive and be more optimistic in entrepreneurship.Write abstracts in English only if the contents are in English or English and Indonesian also fill in Indonesian with a maximum of 200 words. The contents of the background abstract, the method of resolution, the results of the community service/research, discussion of the results achieved and plans for future achievements. TNR typewriting with a size of 10.